A meta-analysis of adjuvant EGFR-TKIs for patients with EGFR mutation of resected non-small cell lung cancer. Issue 47 (25th November 2022) - Cui, Ran; Wei, Chun; Li, Xianyi; Jiang, Ou
Abstract : Background: The role of epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKIs) in improving the prognostic outcome of non-small cell lung cancer (NSCLC) cases harboring EGFR mutation following radical surgery is still controversial. This work focused on comparing EGFR-TKIs and adjuvant chemotherapy (ACT) or placebo in treating NSCLC cases, specifically on those with EGFR-mutant, being in the stage of IB-IIIA and possibly gained benefits from the above treatment after radical resection. Methods: The Cochrane Library, MEDLINE, and Embase databases were searched to identify eligible clinical trials; two authors were responsible for screening the results. The primary outcomes were evaluated by disease-free survival (DFS) and overall survival (OS) based on hazard ratios (HRs) and a relevant 95% confidence interval (CI). Results: The literature search yielded twelve eligible studies, including four retrospective cohort studies and eight randomized controlled trials (RCTs) that enrolled 1694 cases and were of acceptable quality. In patients receiving adjuvant EGFR-TKIs compared with ACT or placebo treatment, HR regarding DFS was 0.47 (95% CI: 0.40, 0.55), whereas the OS rate was 0.74 (95% CI: 0.58, 0.95). For patients who received adjuvant EGFR-TKIs in combination with conventional chemotherapy compared to chemotherapy, the efficiency was significantly enhanced, with the HR for DFS being 0.29 (95% CI: 0.15, 0.58) and that for OS being 0.51 (95% CI: 0.25, 1.04), separately. Conclusion: For NSCLC cases who had EGFR mutations and surgery, adjuvant EGFR-TKI combined with chemotherapy achieved superior effect over chemotherapy or placebo with reference to DFS and may prolong the OS up to some extent.